Spatio-temporal transcriptomic divergence across human and macaque brain development - Zhu, Ying (Science, 2018)
Human nervous system development is an intricate and protracted process that requires precise spatio-temporal transcriptional regulation. Here we generated tissue-level and single-cell transcriptomic data from up to sixteen brain regions covering prenatal and postnatal rhesus macaque development. Integrative analysis with complementary human data revealed that global intra-species (ontogenetic) and inter-species (phylogenetic) regional transcriptomic differences exhibit concerted cup-shaped patterns, with a late fetal-to-infancy (perinatal) convergence. Prenatal neocortical transcriptomic patterns revealed transient topographic gradients, whereas postnatal patterns largely reflected functional hierarchy. Genes exhibiting heterotopic and heterochronic divergence included those transiently enriched in the prenatal prefrontal cortex or linked to autism spectrum disorder and schizophrenia. Our findings shed light on transcriptomic programs underlying the evolution of human brain development and the pathogenesis of neuropsychiatric disorders.